Early molecular replication of human immunodeficiency virus type 1 in cultured-blood-derived T helper dendritic cells. - Langhoff, E (1993)
The rate and efficiency of key steps in the life cycle of the human immunodeficiency virus type 1 was examined in three primary cell types, T cells, monocytes, and T helper dendritic cells using the same quantity of virus involved and same cell number. The results show that viral DNA synthesis proceeds much more rapidly and efficiently in primary T helper dendritic cell populations than in primary T cell and monocyte populations. The increased rate of virus DNA synthesis is attributable either to an increase in the efficiency and the rate of uptake of the virus particles by the T helper dendritic cells, as compared with that in other cell types, or to an increased efficiency and rate of viral DNA synthesis in the T helper dendritic cells. In the subsequent phase of viral expression the appearance of spliced viral mRNA products also occur more rapidly in cultures of primary-blood-derived T helper dendritic cells than is the case in primary T cells and monocytes. The increased efficiency of the early steps of HIV-1 replication in primary-blood-derived T helper dendritic cells than in other blood-derived mononuclear cells raises the possibility that these cells play a central role in HIV-1 infection and pathogenesis.